Transcribing Facial Gestures: Combining Jefferson with the International SignWriting Alphabet (ISWA) - Dix, Carolin (Social Interaction. Video-Based Studies of Human Sociality, 2023)
Within multimodal interaction analysis, transcripts serve not only as a tool for managing the volatility of interaction and catalyzing analytic procedures, but also as an essential medium for making analytic results intersubjectively available. While there are already well-established conventions for transcribing verbal and vocal interactional resources, researchers still struggle with adequately aligning and recognizably representing visual-bodily resources. This contribution provides a practical solution for multimodal transcription, combining conventions of the Jeffersonian system with the sign inventory of the International SignWriting Alphabet (ISWA). The result is a standardized, data oriented, expandable system that relies on iconic depictions rather than on verbal descriptions of visual conduct.